2019
DOI: 10.3390/cells8080830
|View full text |Cite
|
Sign up to set email alerts
|

Bioink Composition and Printing Parameters for 3D Modeling Neural Tissue

Abstract: Neurodegenerative diseases (NDs) are a broad class of pathologies characterized by the progressive loss of neurons in the central nervous system. The main problem in the study of NDs is the lack of an adequate realistic experimental model to study the pathogenic mechanisms. Induced pluripotent stem cells (iPSCs) partially overcome the problem, with their capability to differentiate into almost every cell types; even so, these cells alone are not sufficient to unveil the mechanisms underlying NDs. 3D bioprintin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…Viability was maintained and the hydrogel printed in a 3D structure allowed for the 3D organization of the cells, mimicking the environment of the tissue. These results open the possibility of a new model for the study of ALS, especially in the neuromuscular plaque [70].…”
Section: Hydrogelsmentioning
confidence: 76%
“…Viability was maintained and the hydrogel printed in a 3D structure allowed for the 3D organization of the cells, mimicking the environment of the tissue. These results open the possibility of a new model for the study of ALS, especially in the neuromuscular plaque [70].…”
Section: Hydrogelsmentioning
confidence: 76%
“…Our results suggested that microsphere incorporated scaffolds could potentially generate dopaminergic neurons and a number of committed differentiated neurons. Once optimized, these 3D bioprinted neural tissues could be used to model neurodegenerative diseases using patient-specific hiPSC lines, as currently done in 2D (Poon et al, 2017;Fantini et al, 2019). This study provides an approach to generate 3D neural tissues containing dopaminergic neurons as a clinically relevant model for drug discovery as well as a potential way to generate tissue to replace the lost neurons that die off during Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…hiPSC-derived neuronal and glial precursor cells Neurons (MAP2+); Astrocytes (GFAP+) [35] hiPSC-derived NSCs NSCs (Nestin+/SOX2+/SOX1+/PAX6+) [135] hiPSC-derived neural aggregates Neurons (TUBB3+) [36] hiPSC-derived NPCs Spinal cord motor neurons (TUBB3+/ChaT+); Astrocytes (GFAP+) [136] has made it possible to derive large amounts of human neural cells in vitro. [121] This has largely bypassed the ethical issues of neural cells obtained from either human embryos or embryonic stem cells.…”
Section: Primary Cellsmentioning
confidence: 99%